Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Halophytes and Climate Change: Adaptive Mechanisms and Potential Uses 2019
DOI: 10.1079/9781786394330.0255
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic tolerance mechanisms in halophytes: the case of Tamarix gallica .

Abstract: Toxic compounds in the ecosphere are the consequence of environmental pollution, and have a disruptive influence in the environment. They affect ecosystems, entering food chains and ultimately touching human health. Metal consumption has increased by 300% in the last 50 years and the anthropogenic release of metallic elements such as Pb, Hg, As, Cd, Al and Cr has increased since the beginning of the industrial era. Different strategies have been identified to overcome metallic stress. Knowledge of plant stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Phytomanagement of contaminated soils is of concern also in area affected by salinity (Sghaier et al 2019 ). Atriplex atacamensis , a perennial shrub from Northern Chile occurring on As-contaminated area, may experience transient flooding conditions.…”
Section: Phytoremediation Of As-contaminated Soilsmentioning
confidence: 99%
“…Phytomanagement of contaminated soils is of concern also in area affected by salinity (Sghaier et al 2019 ). Atriplex atacamensis , a perennial shrub from Northern Chile occurring on As-contaminated area, may experience transient flooding conditions.…”
Section: Phytoremediation Of As-contaminated Soilsmentioning
confidence: 99%
“…For example, in Tamarix gallica it was found that the subcellular distribution of As plays an important role in avoiding toxicity of this element and that the greater sequestration of As in vacuoles reduces its toxicity to other cellular organelles in the root. Furthermore, cell wall confinement is a mechanism of leaf tolerance, thanks to which this species has been used in areas for the disposal of industrial and urban effluents contaminated by metals [ 50 ]. The higher CRoot for As at L1 and L2 compared to the Control site is a result of its higher CDTPA in FA in relation to soil, where a higher content of organic matter results in the rapid adsorption of As and a reduction in its mobility [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…T. gallica is considered as an Arsenic-tolerant plant, when the presence of salt gland may play a role in this tolerance. The highest concentration of toxic metals is stored in T. gallica shoots, while the root system is considered as the dominant absorption path for metals (Belhadj-Sgheir et al 2019). Contrary to other halophytes, T. gallica manifested no difference in chlorophyll fluorescence parameters when it was exposed to high arsenic concentration.…”
Section: Action Of Polyphenolic On T Gallica Abiotic Stress Adaptationmentioning
confidence: 92%
“…The leaves are alternate, of a pinkish white green, they are only about 5 mm in diameter, but very numerous, arranged in dense spikes, giving the whole plant a pink coloring. The fruit is a seed topped with a short tuft of hair (Belhadj-Sgheir et al 2019). T. gallica is one of the constituents of Indian traditional herbal recipes, which is hepatotonic, stimulant and has been used traditionally in the treatment of various liver disorders (Bettaib et al 2017).…”
Section: Au6mentioning
confidence: 99%
See 1 more Smart Citation